ChemInform Abstract: C—H Alkenylation of Azoles with Enols and Esters by Nickel Catalysis. Issue 8 (25th February 2014) - Meng, Lingkui; Kamada, Yuko; Muto, Kei; Yamaguchi, Junichiro; Itami, Kenichiro
Abstract The utility of this new title reaction is demonstrated by the synthesis of compound (XVI) which is an intermediate in the synthesis of siphonazole B (XVII).